UMP contributes 600 hand sanitisers for frontliners - UMP, PNC (2020)
As an effort to assist the frontliners to curb the spread of the Covid-19 outbreak, Universiti Malaysia Pahang (UMP) contributed 600 bottles of hand sanitisers: triUMPH (1 L) and hand-carry Germs Free Hand Sanitizer (30 mL).